2001
DOI: 10.1080/019021401300053984
|View full text |Cite
|
Sign up to set email alerts
|

DEFECTIVE GAP JUNCTIONAL INTERCELLULAR COMMUNICATION IN LUNG CANCER: Loss of an Important Mediator of Tissue Homeostasis and Phenotypic Regulation

Abstract: Gap junctions provide direct pathways for the exchange of molecules and ions between neighboring cells, a process known as gap junctional intercellular communication (GJIC). This GJIC is important for homeostasis and regulation of mitosis, differentiation, and apoptosis. Gap junctions are present in lung airway and alveolar epithelial cells and, in addition to the above roles, might coordinate ciliary beating and surfactant secretion. GJIC is decreased in human and mouse lung carcinoma cells because of reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…30,31 Studies have shown that GJIC may progressively decrease during multistage carcinogenesis. 21 Interestingly, a low iodine diet inhibits GJIC in thyroid follicular cells. 32 In the current study, we tested whether GJIC might play a role in iodide-induced bystander tumoricidal effect by the double-dye transfer assays.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30,31 Studies have shown that GJIC may progressively decrease during multistage carcinogenesis. 21 Interestingly, a low iodine diet inhibits GJIC in thyroid follicular cells. 32 In the current study, we tested whether GJIC might play a role in iodide-induced bystander tumoricidal effect by the double-dye transfer assays.…”
Section: Discussionmentioning
confidence: 99%
“…21 A decrease in GJIC activity has been documented in many human malignancies including lung cancer. 21 This may be a consequence of reduced expression of Cx43 and defects in signal transduction pathways that mediate Cx43 function.…”
Section: Iodide Sensitizes Nsclc Cells To Radiation L Zhang Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Also, forced connexin expression can sometimes reduce the tumor-forming capacity of some cell lines (101,233). There may be a role for connexin specificity here, since Cx32 suppressed the tumorforming capacity of a lung carcinoma cell line (234), although Cx43, but not Cx32, conferred growth control to a glioma cell line (101). As a further complication to understanding roles for gap junctions in carcinogenesis, heterocellular communication between tumor cells and endothelial cells appears to be required for transmigration (135).…”
Section: Open and Shut: Gating Connexin Channels And Regulation Of Cementioning
confidence: 99%
“…For instance, tobacco smoke condensates contain substances with the capacity to inhibit gap junctional communication (123,177,183,184,236,237). Cell lines derived from lung tumors are also frequently not coupled through gap junctions, which can be due to a lack of connexin expression or due to constitutively closed gap junction channels (43,233,234). However, not all correlations of changes in connexin expression with tumorigenesis are significant, since reports that Cx37 mutations might be associated with lung cancer (178) were later found to reflect allelic variability in the human Cx37 gene (150).…”
Section: Open and Shut: Gating Connexin Channels And Regulation Of Cementioning
confidence: 99%